Pre-surgical orthopedic treatment with Hinostroza nasal retractor modification in complete unilateral palate fissure. Case report - Hinostroza-Flores, Manuel (2021)
Complete unilateral palatine fissure affects the region of the middle facial third and individuals born with this condition have altered structures on the side where the malformation developed. The objective of the present case report was to describe a pre-surgical orthopedics alternative in a female infant of 1 month 5 days of age with complete unilateral palatine fissure diagnosed with complete unilateral left palatine fissure. The Hinostroza nasal retractor modification was placed, allowing symmetry to the affected nasal structure with respect to the unaffected side. This procedure provides good results, low cost and easy handling and should be considered as an alternative treatment in neonates born with complete unilateral palatine fissure.